Estimation of Slip Distribution of the 2007 Bengkulu Earthquake from GPS Observations Using the LeastSquares Inversion Method - Awaluddin, Moehammad; Meilano, Irwan; Widiyantoro, Sri (Journal of Engineering and Technological Sciences, 2012)
ContinuousÂ  GlobalÂ  PositioningÂ  SystemÂ  (GPS)Â  observationsÂ  showed significantÂ  crustalÂ  displacementsÂ  asÂ  aÂ  resultÂ  ofÂ  theÂ  BengkuluÂ  earthquake occurring on September 12, 2007. A maximum horizontal displacement of 2.11 m was observed at PRKB station, while the vertical component at BSAT station was lifted up with a maximum of 0.73 m, and the vertical component at LAIS station had subsidedÂ  â0.97 m. Adding more constraints on the inversion for the Bengkulu earthquake slip distribution inferred from GPS observations can help solveÂ  theÂ  underdeterminedÂ  least-squaresÂ  inversion.Â  CheckerboardÂ  testsÂ  were performedÂ  toÂ  helpÂ  conductÂ  theÂ  weightingÂ  forÂ  constrainingÂ  theÂ  inversion.Â  The inversion calculation yielded an optimal value for the slip distribution by giving the smoothing constraint a weight of 0.001 and the slip constraint a weight of = 0 at the edge of the earthquake rupture area. The maximum co-seismic slip of the optimal inversion calculation was 5.12 m at the lower area of PRKB station and BSAT station. The seismic moment calculated from the optimal slip distribution was 7.14 x 1021 Nm, which is equivalent to a magnitude of 8.5.